Stereoselectivity evaluation of chiral chitosan microspheres delivery system containing rac-KET in vitro and in vivo - Li-Na Yin; Ya-Wen Zhang; Wen-Hai Huang; Sheng-Hao Wang; Gao-Li Zheng (Taylor & Francis Group, 2019)
The influence of chiral excipient D-chitosan (CS) on the stereoselective release of racemic ketoprofen (rac-KET) microspheres has been investigated in comparison to those microspheres containing individual enantiomers in vitro and in vivo. Stereoselectivity was observed in vitro release test, with R-KET release slightly higher than that of S-KET, especially in 3% rac-KET loading microspheres. Stereoselectivity is dependent on the content of chiral excipient and pH of release medium. A molecular docking study between CS and KET enantiomers further revealed that S-KET has a stronger interaction with CS compared to R-KET. Moreover, the plasma concentration of KET enantiomers in rats shows substantial differences, as the plasma levels of S-KET were higher than those of R-KET. Plasma levels of enantiomers from the R-KET microspheres had similar stereoselectivity as rac-KET microspheres. The S/R ratio of rac-KET microspheres was significantly lower than that of rac-KET suspension (regular-release formulation) (p<.05), and the differences is 3-5 fold. Besides, rates of R-KET converted to S-KET exhibited differences between rac-KET microspheres and suspension. Similar results were also found between R-KET microspheres and suspension. All investigations suggest that the chitosan interacting preferentially with S-KET to R-KET significantly affect the stereoselective pharmacokinetics of rac-KET from chitosan microspheres in rats.